The Clinical and Economic Impact of Point-of-Care CD4 Testing in Mozambique and Other Resource-Limited Settings: A Cost-Effectiveness Analysis. - Hyle, Emily P; Jani, Ilesh V; Lehe, Jonathan; Su, Amanda E; Wood, Robin; Quevedo, Jorge; Losina, Elena; Bassett, Ingrid V; Pei, Pamela P; Paltiel, A David; Resch, Stephen; Freedberg, Kenneth A; et al. (PLoS medicine, 2014)
Point-of-care CD4 tests at HIV diagnosis could improve linkage to care in resource-limited settings. Our objective is to evaluate the clinical and economic impact of point-of-care CD4 tests compared to laboratory-based tests in Mozambique.